Active Learning Strategy in Teaching Rhetoric to the Fourth Semester for the Department of Arabic Language Education at Al-Amien Islamic University - Yusfar Ramadhan; Ainun Sofiya (Universitas Al-Amien Prenduan, 2025)
One of strategies that can create student activity is by emphasizing learning on students, This is called an active learning strategy. So that learning will not be boring because of the full involvement of students in the learning process. The Aims of this research are to determine the process of implementing the active learning strategy used and the factors that hinder and support the learning process of Balaghah students of Arabic Language Education semester IV 2022-2023. Researchers saw the activeness that occurred in students in learning Balaghah in Arabic Education students of IDIA Prenduan. Researchers want to know more about how to apply Balaghah learning so that it is not boring. This research is a qualitative descriptive with data collection in the form of observation, interviews and documentation which used Millis and Huberman's analysis. The evidences and sources of this research were through the learning process in the class. This research showed that the Stategy of Active Learning which is applied by IDIA’s lecturer Prenduan. The course supervisor of Balaghah used by three methods there are: visual based instruction, discussi on class, dan everyone is teacher, With Power Point learning media and ended with an evaluation, namely providing examples related to the material as well as analyzing the Qur'an and giving motivation from lecturers to increase student enthusiasm for learning.Keywords: Strategy, Active Learning, Balaghah.